Psychological resilience and music performance anxiety: exploring mediators and sex differences in Chinese choir members - Du, Hao; Liu, Yanchang; Sun, Jian (Frontiers in Psychology, 2025)
Music performance anxiety (MPA) is a prevalent psychological challenge that can impair musicians' wellbeing and performance quality. While psychological resilience has been proposed as a protective factor, the mechanisms underlying its association with MPA remain unclear, particularly among choir members. This study examined the direct and indirect relationships between psychological resilience and MPA via performance control sense and pre-performance rumination, and further explored whether these pathways differed by sex. A total of 801 Chinese choir members completed validated measures of psychological resilience, performance control sense, pre-performance rumination, and MPA. Structural equation modeling (SEM) was conducted to test mediation effects, and multi-group SEM was used to assess sex differences. Results showed that resilience was negatively associated with MPA both directly and indirectly. Performance control sense emerged as the dominant mediator, accounting for 53.8% of the total effect, while pre-performance rumination accounted for 7.7%. Multi-group analyses indicated significant sex differences: resilience was more strongly linked to reduced rumination in females, the protective effect of control beliefs was stronger among females, and the maladaptive impact of rumination was stronger among males. These findings highlight psychological resilience as a key protective factor in MPA, primarily by enhancing control beliefs and reducing rumination. The study contributes to theoretical understanding of sex-specific mechanisms and suggests practical implications for resilience-based, sex-sensitive interventions in music education and choir practice.